The duration of disgusted and fearful faces is judged longer and shorter than that of neutral faces: the attention-related time distortions as revealed by behavioral and electrophysiological measurements - Zhang, Dandan; Liu, Yunzhe; Wang, Xiaochun; Chen, Yuming; Luo, Yuejia (Frontiers in Behavioral Neuroscience, 2014)
Time perception has been shown to be altered by emotions. This study employed event-related potentials (ERPs) to examine the effects of two threat-related emotions on the judgment of time intervals in the range of 490-910 ms. We demonstrated that disgust and fear have distinct influences on time perception. At the behavioral level, disgusted faces were estimated longer and fearful faces were estimated shorter (i.e., the generalization gradient for the disgusted faces was shifted left while the generalization gradient for the fearful faces was shifted right) when compared with neutral faces. Accordingly, the contingent negative variation, an online ERP index of timing, displayed larger area in disgust and smaller area in fear conditions when compared with neutral condition (disgust = 1.94 ± 2.35 μV•s, neutral = 1.40 ± 2.5 μV•s, and fear = 1.00 ± 2.26 μV•s). These findings indicated that specific neural mechanisms may underlie the attention effects of different subtypes of threat-related emotions on timing; compared with neutral faces, fearful faces are likely to attract more attentional resources while disgusted faces may attract less attentional resources for emotional processing. The major contribution of the current study is to provide neural correlates of fear vs. disgust divergence in the aspect of time perception and to demonstrate beyond the behavioral level that the categorization of threat-related emotions should be refined so to highlight the adaptability of the human defense system.